The mechanism of social media marketing: influencer characteristics, consumer empathy, immersion, and sponsorship disclosure. Issue 8 (30th December 2021) - Jung, Nayoung; Im, Subin
Abstract: Recently, influencer marketing and sponsorship activities have been crucial in marketing communication. This paper explores the relationship between influencers' characteristics (i.e., centrality and trustworthiness), the efficacy of social media posting (i.e., empathy and immersion), and consumers' product attitude. The study further reveals a critical role of sponsorship disclosure in this mechanism. Based on the data from social media users, our findings demonstrated that influencers' centrality and trustworthiness were positively related to consumers' empathic response and immersion toward the social media posting. Consumers' empathy and immersion strongly mediate the link between influencers' characteristics and consumers' attitudes toward the product. Notably, the current study also indicated the moderating role of sponsorship activities and found different effects of centrality and trustworthiness with an apparent sponsorship disclosure. Theoretical and practical implications are further elaborated.